An introduction and performance evaluation of the GRID system for transshipment terminals. (March 2016) - Zhou, Chenhao; Chew, Ek Peng; Lee, Loo Hay; Liu, Daqi
While the global container trade, especially transshipment, keeps growing rapidly, land scarcity and sustainability pose severe challenges to port operators. To maintain their competitiveness, they have to maximize land utilization and improve productivity. As applications of the GRID (Goods Retrieval and Inventory Distribution) system prototype proposed by BEC Industries LLC, this paper discusses two new designs—the single GRID system and hybrid GRID system—from different angles. In particular, the configuration and mechanism of the single GRID system are introduced with different layouts. Given the GRID structure, one of the most critical aspects of the proposed architecture is the high incidence of conflicts among transfer units (TUs). Hence, the authors identify different conflict scenarios and subsequently provide the TU control logic to avoid conflicts. A simulation study then investigates the performance of the single GRID system and its robustness with respect to horizontal and vertical expansion. Due to the limitations of the single GRID system, the hybrid GRID system is then proposed and simulated for terminals demanding huge capacity and productivity. A new flexible and scalable simulation model is designed for the new system. Both the results on land utilization and productivity show that the hybrid GRID system is promising for future transshipment terminals.